Electromagnetic modeling of an active integrated antenna with a MESFET device using MoM-GEC method for UWB applications. Issue 15 (13th October 2019) - Soltani, Takoua; Soltani, Imen; Aguili, Taoufik
Abstract : This paper presents electromagnetic modeling of an active integrated antenna (AIA) with a MESFET device, located inside an infinite rectangular waveguide. This work highlights the influence of the active device in the antenna performance for Ultra Wide Band (UWB) systems. In fact, the method of Moments (MoM) combined with the generalized equivalent circuits (GEC) approach in conjunction with the physical-based small-signal model is applied to compute the input impedance, the reflection coefficient, the current density and the electric field distributions of the AIA resonating at 4 GHz. The physical-based small-signal model was employed to characterize the active device. For validation purpose, the calculated results are compared to the simulated ones on the ADS Agilent simulator. Using S11 < −10 dB technique, it was found that the antenna bandwidth is superior to 500 MHz. In this sense, the collective gain is therefore investigated and calculated for the entire AIA.